Intra-somatosensory cortical circuits mediating pain-induced analgesia - Ji-Ye Huang; Yu-Xin Jin; Wan-Ying Dong; Wan Zhao; Ping-Kai Cheng; Jun-Hao Miao; An Liu; Di Wang; Juan Li; Zhi Zhang; Wenjuan Tao; Xia Zhu (Nature Communications)
Abstract Pain in one part of the body profoundly diminishes the sensation of pain in other parts of the body in humans. Here, we found that pain-related behaviors in hindpaw are inhibited by noxious stimuli from diverse body regions in mice. Using activity-dependent cell labeling in male Fos TRAP2 mice, we captured a neuronal ensemble in the layers 2–4 of secondary somatosensory cortex (S2) that was activated during pain at diverse body regions induced analgesia. Single-cell projection analysis showed that these S2 neurons receive projections from the contralateral S2 and specifically innervate the layer 4 of primary somatosensory cortex (S1). Microendoscopic calcium imaging and chemogenetic manipulation in freely moving mice showed that this S2 → S1 feedforward inhibitory circuit mediates ipsilateral pain-induced analgesia, whereas contralateral S2 innervation of the S2 → S1 circuit mediates contralateral pain-induced analgesia. Our study defines the intra-somatosensory cortical circuits underlying “pain inhibiting pain”, expanding the scope of known circuit mechanisms involved in pain relief.